Reduction of dietary obesity in aP2-Ucp transgenic mice: physiology and adipose tissue distribution - Kopecký, J; Hodný, Z; Rossmeisl, M; Syrový, I; Kozak, L P (The American journal of physiology, 1996)
We seek to determine whether increased energy dissipation in adipose tissue can prevent obesity. Transgenic mice with C57BL6/J background and the adipocyte lipid-binding protein (aP2) gene promoter directing expression of the mitochondrial uncoupling protein (UCP) gene in white and brown fat were used. Physiologically, UCP is essential for nonshivering thermogenesis in brown fat. Mice were assigned to a chow or a high-fat (HF) diet at 3 mo of age. Over the next 25 wk, gains of body weight were similar in corresponding subgroups (n = 6-8) of female and male mice: 4-5 g in chow nontransgenic and transgenic, 20 g in HF nontransgenic, and 9-11 g in HF transgenic mice. The lower body weight gain in the HF transgenic vs. nontransgenic mice corresponded to a twofold lower feed efficiency. Gonadal fat was enlarged, but subcutaneous white fat was decreased in the transgenic vs. nontransgenic mice in both dietary conditions. The results suggest that UCP synthesized from the aP2 gene promoter is capable of reducing dietary obesity.
Keywords: homeostáza; Glucose; Male; Obesity; přijímání potravy; Uncoupling Protein 1; adaptorový proteinový komplex 2; tuková tkáň; membránové proteiny; Adaptor Protein Complex alpha Subunits; Membrane Proteins; Homeostasis; obezita; iontové kanály; glukosa; mužské pohlaví; Dietary Fats; Eating; metabolismus lipidů; mitochondriální proteiny; Body Weight; Ion Channels; Carrier Proteins; Mitochondrial Proteins; dietní tuky; Adaptor Protein Complex 2; adaptorový proteinový komplex - alfa-podjednotky; Animals; Adipose Tissue; ženské pohlaví; myši transgenní; uncoupling protein 1; zvířata; Lipid Metabolism; adaptorové proteiny vezikulární transportní; složení těla; myši inbrední C57BL; myši; Adaptor Proteins, Vesicular Transport; Body Composition; Mice, Inbred C57BL; Mice; Female; tělesná hmotnost; transportní proteiny; Mice, Transgenic